Membangkitkan Ekonomi Dhuafa: Pemberdayaan Keluarga Dhuafa Melalui Usaha Takoyaki dan Papeda - Hanum Allya Zulfani; Ela Puspta Sari; Elsha Salsabilah; Ilham Mundzir (CV SWA Anugerah, 2024)
The Covid-19 pandemic in Indonesia triggered the Large-Scale Social Restrictions (PSBB) policy, which resulted in significant changes to the socio-economic activities of the community. The impact is felt widely, especially on the continuity of employment and workers' income. In the early stages, the International Labor Organization (ILO) estimates that around 25 million global jobs could be lost due to the Covid-19 pandemic. A significant reduction in working hours is also predicted, with a potential loss of 305 million full-time jobs by the second quarter of 2020. The community service program was carried out in Babakan Gempol Village, Tangerang, to empower poor families, especially Mrs. Sri Wahyuni who was affected by layoffs. Through a Participatory Action Research (PAR) approach, this program provided business capital to open a takoyaki and papeda business, which succeeded in increasing the family's daily income from Rp. 150,000 to Rp. 185,000. This activity shows that economic empowerment through small businesses can help poor families achieve a more prosperous life. Keyword: Duafa family, Covid-19, Entrepreneurship